Electrode Materials Engineering in Electrocatalytic CO2 Reduction: Energy Input and Conversion Efficiency - Song, Rong‐Bin; Zhu, Wenlei; Fu, Jiaju; Chen, Ying; Liu, Lixia; Zhang, Jian‐Rong; Lin, Yuehe; Zhu, Jun‐Jie (Advanced materials (Weinheim), 2020)
Electrocatalytic CO2 reduction (ECR) is a promising technology to simultaneously alleviate CO2‐caused climate hazards and ever‐increasing energy demands, as it can utilize CO2 in the atmosphere to provide the required feedstocks for industrial production and daily life. In recent years, substantial progress in ECR systems has been achieved by the exploitation of various novel electrode materials. The anodic materials and cathodic catalysts that have, respectively, led to high‐efficiency energy input and effective heterogenous catalytic conversion in ECR systems are comprehensively reviewed. Based on the differences in the nature of energy sources and the role of materials used at the anode, the fundamentals of ECR systems, including photo‐anode‐assisted ECR systems and bio‐anode‐assisted ECR systems, are explained in detail. Additionally, the cathodic reaction mechanisms and pathways of ECR are described along with a discussion of different design strategies for cathode catalysts to enhance conversion efficiency and selectivity. The emerging challenges and some perspective on both anode materials and cathodic catalysts are also outlined for better development of ECR systems. Electrode materials are considered to be important components for electrocatalytic CO2 reduction systems, as they affect the energy input method and CO2 conversion efficiencies. Various photo‐anode and bio‐anode materials for lowering external bias and progress on cathode catalysts for improving CO2 conversion efficiencies are comprehensively reviewed. Moreover, enhancement strategies in the design of these electrode materials are highlighted.